Sleep Biomarkers for Predicting Cognitive Decline and Alzheimer's Disease: A Systematic Review of Longitudinal Studies. - Carpi, Matteo; Fernandes, Mariana; Mercuri, Nicola Biagio; Liguori, Claudio (J Alzheimers Dis, 2024)
BACKGROUND: Sleep disturbances are considered a hallmark of dementia, and strong evidence supports the association between alterations in sleep parameters and cognitive decline in patients with mild cognitive impairment and Alzheimer's disease (AD). OBJECTIVE: This systematic review aims to summarize the existing evidence on the longitudinal association between sleep parameters and cognitive decline, with the goal of identifying potential sleep biomarkers of AD-related neurodegeneration. METHODS: Literature search was conducted in PubMed, Web of Science, and Scopus databases from inception to 28 March 2023. Longitudinal studies investigating the association between baseline objectively-measured sleep parameters and cognitive decline were assessed for eligibility. RESULTS: Seventeen studies were included in the qualitative synthesis. Sleep fragmentation, reduced sleep efficiency, reduced REM sleep, increased light sleep, and sleep-disordered breathing were identified as predictors of cognitive decline. Sleep duration exhibited a U-shaped relation with subsequent neurodegeneration. Additionally, several sleep microstructural parameters were associated with cognitive decline, although inconsistencies were observed across studies. CONCLUSIONS: These findings suggest that sleep alterations hold promise as early biomarker of cognitive decline, but the current evidence is limited due to substantial methodological heterogeneity among studies. Further research is necessary to identify the most reliable sleep parameters for predicting cognitive impairment and AD, and to investigate interventions targeting sleep that can assist clinicians in the early recognition and treatment of cognitive decline. Standardized procedures for longitudinal studies evaluating sleep and cognition should be developed and the use of continuous sleep monitoring techniques, such as actigraphy or EEG headband, might be encouraged.
Keywords: Alzheimer Disease; Biomarkers; Cognition; Cognitive Dysfunction; Humans; Longitudinal Studies; Sleep

Cerebrospinal Fluid sTREM-2, GFAP, and β-S100 in Symptomatic Sporadic Alzheimer's Disease: Microglial, Astrocytic, and APOE Contributions Along the Alzheimer's Disease Continuum. - Bonomi, Chiara Giuseppina; Assogna, Martina; Di Donna, Martina Gaia; Bernocchi, Francesca; De Lucia, Vincenzo; Nuccetelli, Marzia; Fiorelli, Denise; Loizzo, Stefano; Mercuri, Nicola Biagio; Koch, Giacomo; Martorana, Alessandro; Motta, Caterina (J Alzheimers Dis, 2023)
BACKGROUND: Many transversal mechanisms act synergistically at different time-points in the cascade of Alzheimer's disease (AD), since amyloid-β (Aβ) deposition, tau pathology, and neuroinflammation influence each other. OBJECTIVE: We explored the contributions of microglia and astrocytes in patients with symptomatic sporadic AD stratified according to AT(N) system and APOE genotype. METHODS: We compared the cerebrospinal fluid (CSF) levels of sTREM-2 and markers of astrocytic activation (GFAP; β-S100) from 71 patients with AD (23 A+T-,48 A+T+; 38 APOEɛ3, 33 APOEɛ4) and 30 healthy controls (HC). With multivariate analyses we investigated associations between glial biomarkers, Aβ42, and p-tau in all subgroups. RESULTS: CSF sTREM-2 was higher in A+T+ [1.437 (0.264)] and A+T- [1.355 (0.213)] than in HC [1.042 (0.198); both p < 0.001]; GFAP and β-S100 were comparable across groups. Considering all patients, sTREM-2 positively associated with Aβ42 (p = 0.04) and p-tau (=0.016), with the first being present only in the A+T- subgroup (p = 0.023). GFAP positively associated with Aβ42 in all patients (p = 0.020) and in the A+T+ subgroup (p = 0.04). Stratifying by APOE, a positive association of sTREM-2 and p-tau was confirmed selectively in carriers of ɛ4 (p = 0.018). Finally, sTREM-2 positively correlated with β-S100 in all subgroups, and with GFAP in A+T+ (p = 0.042). CONCLUSION: Our results confirm the increase of CSF sTREM-2 in AD, which associates with reduced amyloidopathy in A+T- patients. Moreover, microglial activation seems to increase CSF tau levels in carriers of APOEɛ4, is associated with astrocytic reactivity (GFAP) in A+T+, and likely leads the acquisition of a more neurotoxic astrocytic phenotype (β-S100).
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Apolipoproteins E; Astrocytes; Biomarkers; Humans; Microglia; Peptide Fragments; tau Proteins

Sleep-Wake Cycle in Alzheimer's Disease Is Associated with Tau Pathology and Orexin Dysregulation. - Liguori, Claudio; Spanetta, Matteo; Izzi, Francesca; Franchini, Flaminia; Nuccetelli, Marzia; Sancesario, Giulia Maria; Di Santo, Simona; Bernardini, Sergio; Mercuri, Nicola Biagio; Placidi, Fabio (J Alzheimers Dis, 2020)
BACKGROUND: Alzheimer's disease (AD) is the most common form of dementia. It is mainly characterized by a progressive deterioration of cognition, but sleep-wake cycle disturbances frequently occur. Irregular sleep-wake cycle, insomnia, and daytime napping usually occur in patients with AD in the course of the disease. OBJECTIVE: The aim of the present study was to verify the sleep-wake cycle in mild to moderate AD patients compared to controls, and to evaluate the relationship between the sleep-wake cycle impairment and the neuropsychological testing, CSF AD biomarkers, and CSF orexin concentrations. METHODS: Mild to moderate AD patients were enrolled and underwent 14-day actigraphic recording, sleep diary, neuropsychological testing, and CSF biomarkers analysis. All patients were compared to controls. RESULTS: Eighteen AD patients were compared to ten controls. AD patients showed the alteration of the sleep-wake cycle, featured by sleep dysregulation and daytime wake fragmentation, with respect to controls. Considering the correlation analysis, we documented the correlation between tau proteins and orexin CSF levels and sleep-wake cycle dysregulation. CONCLUSION: This study confirmed the dysregulation of sleep-wake cycle in AD patients, as reflected by the daytime wake fragmentation, irregular sleep-wake rhythm, and nocturnal sleep impairment. This sleep-wake cycle disorder correlates with AD neuropathological in vivo features and brain orexin activity. Hence, we suppose that a more marked AD pathology coupled with orexinergic system dysregulation may promote sleep-wake cycle impairment in AD patients.

Amyloid-Mediated Cholinergic Dysfunction in Motor Impairment Related to Alzheimer's Disease. - Schirinzi, Tommaso; Di Lorenzo, Francesco; Sancesario, Giulia Maria; Di Lazzaro, Giulia; Ponzo, Viviana; Pisani, Antonio; Mercuri, Nicola Biagio; Koch, Giacomo; Martorana, Alessandro (J Alzheimers Dis, 2018)
BACKGROUND: Although motor disturbances parallel the course of dementia, worsening both quality of life and social costs, the pathogenesis remains still unclear. OBJECTIVE: Through the combination of cerebrospinal fluid (CSF) biomarkers assessment and transcranial magnetic stimulation (TMS) protocols, here we provided a cross-sectional study to understand pathogenic mechanisms of Alzheimer's disease (AD)-related early motor disturbances. METHODS: The motor phenotype, as defined with Unified Parkinson's Disease Rating Scale (UPDRS) part 2-3, Rating Scale for Gait Evaluation in Cognitive Deterioration (RSEGCD) and Tinetti scale, together with CSF profile of amyloid-β 42 (Aβ42), total-tau, and phosphorylated-tau were determined in 37 AD patients and compared to 18 patients with vascular dementia (VaD). A TMS protocol of short afferent inhibition (SAI) was further applied on a subset of AD patients. Clinical, biochemical, and neurophysiological data were then compared and correlated in order to find significant associations. RESULTS: AD patients exhibited subtle locomotor impairment and slight extrapyramidal signs. Main motor features (UPDRS part 3, RSGECD, and Tinetti scale scores) correlate with Aβ42 levels but not with t-tau and p-tau. AD patients also presented SAI impairment directly related to UPDRS part 3 score and Aβ42 levels. Motor disturbances of VaD group did not differ statistically from AD and did not correlate with CSF biomarkers. CONCLUSIONS: The association of motor disturbances with low Aβ42 CSF levels and individual SAI suggests that amyloid-mediated degeneration of cholinergic system may account for early AD-related motor impairment, providing interesting insights either for frailty stratification of patients or personalized therapies.

Cerebrospinal Fluid Orexin Levels and Nocturnal Sleep Disruption in Alzheimer's Disease Patients Showing Neuropsychiatric Symptoms. - Liguori, Claudio; Mercuri, Nicola Biagio; Nuccetelli, Marzia; Izzi, Francesca; Bernardini, Sergio; Placidi, Fabio (J Alzheimers Dis, 2018)
BACKGROUND: Alzheimer's disease (AD) is the most common form of dementia. It is characterized by a progressive deterioration of cognition, frequently associated with neuropsychiatric symptoms (NPS). Among NPS, sleep disturbances often affect AD patients. Orexinergic system dysregulation has been associated with sleep impairment in AD patients. OBJECTIVE: The present study investigated CSF orexin levels in AD patients and their relationship with both NPS, measured by the neuropsychiatric inventory (NPI), and sleep, measured via polysomnography. METHODS: This is a secondary analysis of a previous study investigating CSF biomarkers, sleep impairment and cognitive decline in AD patients. AD patients completing the NPI were included in this analysis and distributed in two groups based on the presence (NPI score ≥4, AD/NPS+) or absence (NPI score <4, AD/NPS-) of NPS. RESULTS: Twenty-two AD patients constituted the AD/NPS+ group and 20 patients constituted the AD/NPS-group. We observed higher CSF orexin levels in AD/NPS+ than AD/NPS-patients. Moreover, AD/NPS+ showed a more fragmented and the reduction of REM sleep compared to AD/NPS-patients. Notably, higher NPI scores correlated with a more altered sleep structure, higher CSF orexin levels and lower MMSE scores. CONCLUSION: This study documented that AD patients showing NPS present a more fragmented sleep coupled with higher CSF orexin levels compared to AD patients not affected by NPS. This finding showing the increased orexinergic tone in AD patients affected by NPS suggests the possible influence of the orexinergic system dysregulation not only on sleep impairment but also on neurobehavioral disturbances.